Desafios e oportunidades para a implantação do VLT no Brasil - Ribeiro, Euclides Aparecido (2015)
The identification of aspects and circumstance considered as challenges and opportunities inherent in the implementation of the urban transport system operated by the Light Rail Transit - LRT in Brazilian cities are at the heart of the goals of this work. Developed a methodology where theoretical research done through the literature review and the application of Delphi method, used for the query to a group of subject matter experts, formed the basis for completion of the study. The results show its role of facilitator and propellant within the context of urban policies in cities where it already operates on a consolidated basis in several countries, creating expectations that can achieve the same effects in Brazilian cities, which will be deployed and that way, if firm as an efficient urban transport mode, an agent of sustainable urban mobility. It is concluded that, given the reality of urban mobility conditions in most Brazilian cities large and medium-sized, the opportunities for this innovative transport system and holder of proactive features, observed by the methodology applied, are feasible, since , its viability is proven through studies covering aspects such as; the existence of demand, the investment capacity of the governing body, the prospect of financial return and integration with existing modes, to name the most important. Also through the applied methodology, it can be concluded that the challenges for its implementation in the country are of great proportions, starting with the high investments required, through the formulation of policies that integrate the various segments of urban management and culminating with the effective participation of population most interested. Thus, it is understood that the opportunities and challenges for the VLT go hand in hand, on the prowl for decisions that put to the test.